Meisterfeldia bitsevi—new testate amoeba of the family Cryptodifflugiidae Jung, 1942 (Amoebozoa: Arcellinida) from the tree hollow in the urban park (Moscow, Russia) with a key to species of the genus Meisterfeldia - Bobrov, Anatoly; Mazei, Yuri (Zootaxa, 2021)
The new testate amoeba species Meisterfeldia bitsevi is described from the linden-tree trunk hollow in the urban park in Moscow (Russia). New species is characterized by elongated ovoid bilaterally symmetrical shell, which is laterally not compressed. The shell is composed of proteinaceous material without mineral particles. Almost circular subterminal aperture is placed on ventral side. The key to the species of the genus Meisterfeldia is developed.